Exploring Determinants of Entrepreneurial Readiness on Sukses Berkah Community’s Member - Arik Wulandari; Agus Hermawan; Imam Mukhlis (Profesional Muda Cendekia Publishing, 2021)
This article aims to determine (1) the effect of motivation, opportunity identification, resources, and entrepreneurial abilities on entrepreneurial readiness; and (2) the role of entrepreneurship training as a moderating variable on motivation, opportunity identification, resources, and entrepreneurial abilities on entrepreneurial readiness. This research is a quantitative study using proportional random sampling with a total of 200 respondents. Data collection used a questionnaire whose results analyze by Moderated Regression Analysis (MRA). The results showed a positive and significant effect of motivation, opportunity identification, resources, entrepreneurial ability, and entrepreneurship training that could moderate the impact of all these factors on entrepreneurial readiness. Based on this research results, it can know that to start entrepreneurship requires the motivation to exert all efforts, opportunity identification to find and implement potential in business, resources to increase competitive business advantage, and entrepreneurial ability to achieve business success using all its capabilities. Entrepreneurship training can improve these factors. The better the entrepreneurship training follows, the more positive impact on improving the readiness to start a thriving Sukses Berkah Community (SBC) member.